History of Christian Missions in Baotou and Surrounding Areas: Records of Swedish pastors in Inner Mongolia - ZHANG, Haifeng (Journal of Research for Christianity in China (JRCC), 2025)
This article, based on James Hudson Taylor's China Inland Mission, Erik Folke's Swedish Mission in China, the Albert Benjamin Simpson's Christian and Missionary Alliance and Fredrik Franso's The Scandinavian Alliance Mission, records the history of Christian mission in Baotou and the surrounding areas in detail, covering the entire process from the beginning of the missionary work in the Baotou area by Western missionaries, mainly Swedish missionaries, to their departure from China in 1950s. The first part records the introduction of Christianity to Baotou and the four main missionary organization that entered the area. The second part covers the missionary process of the various missionary organizations in Baotou and the surrounding area from 1882 to the 1900 disaster. The fourth part records the rapid development of the missionary process from the 1900 to the founding of the state; the appendix records the brief experience of a local missionary trained by Swedish missionaries in Baotou who became a preacher and pastor. This article records in detail the relationship between missionaries and missionary organizations  around Baotou, as well as a brief account of their missionary experiences, with a collection of photographs of some of the missionaries and some historical photographs in the article.
Keywords: Baotou, Chrisitanity, Sweeden Missionaries, History of Mission